2013
DOI: 10.2174/1874213001306010010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, Dietary and Temporal Niche Dimensions in Ecological Segregation of Two Sympatric, Congeneric Marsupial Species

Abstract: Didelphis aurita and D. albiventris are widely distributed in South America, with a range of sympatry in the limit of their distribution, particularly in Araucaria mixed ombrophilous forest in the southern Atlantic Forest. We investigated the spatial, feeding, and time use between these morphologically similar species in a remnant of Araucaria forest in southern Brazil for one year. We tested the hypothesis that these species when in sympatry segregate each other in space use, diet, and/or activity time. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…In the NRW‐NNR, niche differentiation between M. leonina and M. mulatta was revealed in both space and time, and occurred in at least one dimension, as generally suggested by Cáceres and Machado (2013). Schoener (1974) had concluded “Habitat dimensions are important more often than food‐type dimensions, which is important more often than temporal dimension”.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the NRW‐NNR, niche differentiation between M. leonina and M. mulatta was revealed in both space and time, and occurred in at least one dimension, as generally suggested by Cáceres and Machado (2013). Schoener (1974) had concluded “Habitat dimensions are important more often than food‐type dimensions, which is important more often than temporal dimension”.…”
Section: Discussionsupporting
confidence: 68%
“…Defined as the sum of habitat requirements and behaviors of a given species, a niche is multidimensional and includes the distribution, resource‐utilization, dietary requirements, seasonality, and activity rhythm of the species, among other factors (Grinnell, 1917; Hutchinson, 1957). To coexist stably, the niches of sympatric species should differ significantly in at least one dimension (Cáceres & Machado, 2013). Previous studies on primates showed patterns of spatial and temporal fluctuations in various niche dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also highlighted the fact that some species have a greater degree of avoidance to human presence than others (Burger and Gochfield 1991;Smit and Visser 1993;Rodgers and Smith 1995;Gill et al 2001Gill et al , 2007. This is not surprising since closely related species tend to differ ecologically, leading to use of different niche dimensions (Schoener 1974;Caceres and Machado 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of similar species that share resources in the environment is of central interest in community ecology (Begon et al 2006;Atie´nzar et al 2013). Theory stipulates that to coexist, co-occurring species should differ on at least one dimension of their ecological niche (Caceres and Machado 2013). They should use space differently at a small scale.…”
Section: Introductionmentioning
confidence: 99%
“…food, space/microhabitat, and time) (Schoener, ; Maci and Basset, ). Habitat is the niche axis most frequently partitioned when compared to time and food (Schoener, ; Toft, ; Hofer et al., ), since different use of the space may result in alternative diets for such species, implying possible competitive effects between species (Cáceres and Machado, ). Moreover, whether the observed segregation between the two organisms is caused by competition or by chance can be determined by the null model to compare the expectations (Hofer et al., ).…”
Section: Introductionmentioning
confidence: 99%